PERANCANGAN JARINGAN FIBER TO THE HOME (FTTH) MENGGUNAKAN TEKNOLOGI GIGABIT PASSIVE OPTICAL NETWORK (GPON) - Prayoga, Wira Maulana; Sani, Asrul (EBID: Ekonomi Bisnis Digital, 2023)
The development of technology that we use today is increasingly developing, especially in the world of telecommunications. Rapid changes in telecommunications networks are also driven by users' need to stay connected anytime and anywhere. Various new application features such as multimedia services, video conferencing, online games and internet services require larger bandwidth at high speeds. The aim of this research is to understand the basic concepts of Fiber To The Home network design, to obtain a Fiber To The Home access network design based on the location of device placement in the FTTH network design, to analyze the Link Power Budget parameters as a sign of the feasibility of the FTTH network design results, and to find out implementation of Gigabit Passive Optical Network (GPON). The data collection methods used are literature methods, observation methods, and analysis techniques. The results of the research, the basic concept of Fiber To The Home network design is easy for users to understand, the location of device placement in the FTTH network design can be obtained based on the Fiber To The Home access network design, the Link Power Budget parameter as a sign of the feasibility of the FTTH network design results can be used as an analysis reference, and Gigabit Passive Optical Network (GPON) can be applied to FTTH network design.